Assessment of the rarity and conservation status of the Colombian endemic brown hairy dwarf porcupine Coendou vestitus. Issue 5 (17th September 2021) - Torres-Martínez, María M.; Ramírez-Chaves, Héctor E.; Noguera-Urbano, Elkin A.; Passos, Fernando C.
Abstract: The brown hairy dwarf porcupine Coendou vestitus is a poorly studied Andean species endemic to Colombia. Its current Red List category is contradictory: globally it is categorized as Data Deficient but in Colombia it is categorized as Vulnerable. This contradiction has limited the implementation of conservation programmes. We evaluate the level of rarity of the species and provide consolidated information for a new assessment of its Red List status. We reviewed literature, photographs, and voucher specimens in natural history collections. Using the confirmed records, we estimated the extent of occurrence (EOO) based on the minimum convex polygon and the area of occupancy (AOO) summing the area of grid squares occupied by the species. We found that C. vestitus is very rare, with a small range, low estimated population density, occurrence in only one habitat type and small body size. The species has an EOO of 3, 323 km 2 and an AOO of 24 km 2, based on six confirmed localities, all on the western slopes of the Eastern Cordillera, in the central Andean region of Colombia. Based on the species' rarity, restricted distribution, and threats to its natural habitat, we recommend its categorization as Endangered on the IUCN Red List. This will help delineate research and conservation efforts for this porcupine, which has a highly restricted range and inhabits the threatened Andean forest.